The Relationship of Parents' Parenting Patterns with Online Game Addiction During The Covid-19 Pandemic at SMK Mekanika Cirebon - Siti Lia Amaliah; Iman Permana (Eduvest - Journal of Universal Studies, 2022)
Since the outbreak of Covid-19, the activities of parents and children have changed, many parents who experience stress due to their business experiencing a decrease in income and even going out of business, while some have to work at home using the WFH (Work From Home) system set by other companies and institutions. . Stress conditions experienced by parents have a relationship with the parenting style given by parents to their children, there is a statistically significant relationship between the stress conditions of parents and the parenting style of parents for their children The purpose of this study was to analyze the relationship between parenting and online game addiction at SMK Mekanika Cirebon. The method used is descriptive quantitative with survey research. Data collection by questionnaire. 220 Participants were taken by proportional random sampling. Data analysis with simple regression test method with the help of SPSS. Based on the values ​​obtained, it shows that the percentage of the influence of the parenting style variable on online game addiction is 22, 28%, while the remaining 7.72% is influenced by other variables not examined in this study. This study concludes that the characteristics of respondents consist of the work of parents of private employees, students in class XII are male with a duration of playing games more than 3 hours/day. The parenting pattern used by parents for students at SMK Mekanika Cirebon is democratic parenting, the level of addiction game online on students at SMK Mekanika Cirebon